Statistical Moments between Theory and Computational Applications using MAPLE and R Programs - Asselhab محمد عبدالله (Journal of Pure & Applied Sciences, 2021)
There are many scientific topics to be far away from practical sides and limited to theatrical one, that may be because of; huge data, complicated hand computations, requiring accuracy results, the human efforts may be unable to do it. Teaching statistics suffering from that. Statistical moments are one of the topics which listed in this context. This paper aimed to develop a practical method to teach statistics, concerning to describing data using statistical moments by employing the two technician programs; Maple program (computer algebra system CAS), and R program (interactive environment for statistical computing). The paper followed; presenting a theoretical view about algebra of moments, practically it is implementing two computational applications relating to using moments to describing data with simplified and interesting method to both teachers and students.